Medicinal plants of Teesta Valley, Darjeeling district, West Bengal, India: A quantitative ethnomedicinal study - Yasodha Subba, Samik Hazra, Chowdhury Habibur Rahaman (Journal of Applied Pharmaceutical Science, 2023)
The present paper offers considerable information on therapeutic plants used traditionally by the residents of Teesta Valley in Darjeeling district, West Bengal. For the acquisition of ethnomedicinal information, semi-structured interviews were conducted with 28 knowledgeable people. The Free, Prior Informed Consent was taken from each participant prior to the collection of field data. A total of 74 species belonging to 68 genera and 44 families were documented to treat 42 types of health conditions. Leaf (30.77%) was mostly used in the preparation of traditional herbal medicines. Collected ethnobotanical data have been evaluated using suitable statistical tools like fidelity level (FL%), informant consensus factor (Fic) and importance value index (IVs). Highest Fic were reported from digestive system disorders. In FL%, highest score (92.8%) was observed in the plants Drymaria cordata (L.) Roemer & Schultes and Zingiber officinale Roscoe. The highest score for IVs was noticed in cases of Centella asiatica (L.) Urb., Artemisia nilagirica (C.B. Clarke) Pamp., and Terminalia chebula Retz. This documentation will enhance the database on ethnomedicine of the district as well as the country, but scientific validation of the documented ethnomedicinal claim is required.
Keywords: Ethnomedicine, Teesta Valley, informant consensus factor, fidelity level, importance value index